Routine clinical use of liraglutide 3 mg for the treatment of obesity: Outcomes in non‐surgical and bariatric surgery patients. Issue 6 (25th March 2019) - Suliman, Mohamed; Buckley, Adam; Al Tikriti, Alia; Tan, Tricia; le Roux, Carel W.; Lessan, Nader; Barakat, Maha
Abstract : In this study we prospectively collected data on the use of liraglutide 3 mg in obese Arab patients. As part of routine care, 2092 patients were dispensed liraglutide 3 mg. Median age was 38 years and 77% were women. Median baseline weight was 95 kg and body mass index was 36.6 kg/m 2 . Of the patients, 188 (9%) had previous bariatric surgery. Seven hundred and eighty‐seven patients were treated for ≥16 weeks and their median (interquartile range) weight loss was 6.0 (2.4‐9.4) kg, equivalent to 6.4% (2.6%‐9.7%) of baseline weight ( P < 0.0001, n = 787). Of those treated for ≥16 weeks, 474 (60%) achieved a weight loss of >5% of baseline weight while 182 (23%) achieved >10% weight loss. There was no difference in percentage weight loss between postbariatric surgery (n = 76) and non‐surgical patients (n = 711). As a result of adverse events, mainly gastrointestinal symptoms, 140 (6.7%) of the patients stopped treatment. One patient developed acute pancreatitis in the context of gallstone disease but made an uneventful recovery. Liraglutide 3 mg was well tolerated and resulted in weight loss in routine clinical care similar to that seen in randomized controlled trials.